2010
DOI: 10.1016/j.jmb.2010.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Nebulin: A Study of Protein Repeat Evolution

Abstract: Protein domain repeats are common in proteins that are central to the organization of a cell, in particular in eukaryotes. They are known to evolve through internal tandem duplications. However, the understanding of the underlying mechanisms is incomplete. To shed light on repeat expansion mechanisms, we have studied the evolution of the muscle protein Nebulin, a protein that contains a large number of actin-binding nebulin domains.Nebulin proteins have evolved from an invertebrate precursor containing two neb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 42 publications
3
42
1
Order By: Relevance
“…Nebulin is the largest member of an evolutionary conserved tandem-repeat protein family in vertebrates (Bjorklund et al, 2010). Members of this family include nebulin, N-RAP, LASP-1, LASP-2 and nebulette (Kontrogianni-Konstantopoulos et al, 2009;Labeit et al, 2011;Pappas et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Nebulin is the largest member of an evolutionary conserved tandem-repeat protein family in vertebrates (Bjorklund et al, 2010). Members of this family include nebulin, N-RAP, LASP-1, LASP-2 and nebulette (Kontrogianni-Konstantopoulos et al, 2009;Labeit et al, 2011;Pappas et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the TRI region is the result of two tandem duplications through Alu-mediated homologous recombination in an ancestor of human and chimpanzee. 14 One of the most common mechanisms inducing CNVs is thought to be non-allelic homologous recombination (NAHR) caused by misalignment and cross-over of non-allelic homologous DNA segments, such as low copy repeats. CNV breakpoints have also been shown to frequently reside in regions of repeat elements.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of repeated proteins it is clear that the duplication of particular domain combinations are strongly favored [8]. The large length variation caused by indels of several protein repeat domains affects binding properties of the proteins, i.e.…”
Section: Introductionmentioning
confidence: 99%